PENGARUH PERPUTARAN KAS DAN LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR PERBANKAN INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 (THE IMPACT OF COVID PANDEMIC) - Fransiskus Marlon Reu (P3M- Politeknik Negeri Kupang, 2023)
The research conducted by the author aims to determine the effect of cash turnover and leverage on profitability (ROA) in banking sector companies listed on the IDX LQ45 index. The data analysis technique in this study is quantitative data analysis, which is to accurately test and analyze data in the form of numbers. The data collection technique in this study is a documentation study by viewing and collecting financial statement data relating to cash turnover and leverage. The results showed that cash turnover had a significant effect on profitability (ROA). Leverage has a significant effect on profitability (ROA). Then cash turnover and leverage affect profitability (ROA) simultaneously.